Knowledge and practice of nursing personnel regarding infection prevention at om hospital and research center, Chabahil, Kathmandu. - Sapkota, Sita (2008)
ABSTRACT: This study has been under taken for the partial fulfillment of requirement for the degree of Bachelor in Hospital Nursing at Om Health Campus, Chabahil. This study was conducted on "Knowledge and practice of Nursing Personnel Regarding Infection Prevention.". Objective of this study was to assess the knowledge of nursing personnel about Infection prevention who are working in different wards of Om Hospital and Research center. The study design was descriptive in nature. A sample of 50 nurses, who were working in different wards of Om Hospital and Research center, was used for the purpose of this study. Sample of the nurses was selected purposively. Primary data were collected by requesting selected nurses to fill up the structured questionnaire ,validity and reliability of the tools were maintained by preliminary testing, experts advice and ethical consideration through out the study. Data were analysed using descriptive technique. Major knowledge area found that 100% respondents had heard about Infection prevention and only 46% of respondents had knowledge on infection prevention.Only 18% had attained the training about infection prevention.Knowledge of protective barriers to prevent the spread of infections were 86%.96% of respondents had knowledge about blood born disease and 90% of respondents were known the blood born disease.Only 34% of respondents had knowledge about antisepsis and 62% were knowledge of preparing of 0.5% of chlorine solution.100% of respondents were reused the gloves and only 38 % had knowledge about right method of processing. It found that there should be provided training timely to have better knowledge of infection prevention and practice of activities. There also be needed infection prevention committee which can regulate all activities by preventing potential infection.